Optimization Of Sharia Micro Credit Financing As An Inclusive Solution For Msmes: Swot Analysis Approach: (Case Study: Bsi Kanwil S Parman) - Ayunda Syapa Azra; Fauzi Arif Lubis; Muhammad Syahbudi (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the optimization of Sharia People's Business Credit (KUR) financing as an inclusive solution for MSMEs, using a case study at Bank Syariah Indonesia (BSI) S. Parman Medan Regional Office. Using a qualitative descriptive-analytical approach, data was collected through interviews with three financing marketers. The results show that Sharia KUR plays a crucial role in reaching MSMEs that have been underserved by formal banking. BSI's humanistic, religious, and educational approach has successfully built customer trust and loyalty. However, several challenges remain, such as low sharia financial literacy, inefficient administrative processes, and competition from loan sharks offering faster processing times, even though they are detrimental to customers. Nevertheless, the potential growth of MSMEs in the culinary and halal livestock sectors opens up significant opportunities for the expansion of this financing. In conclusion, Sharia KUR is not only a sharia-based financing alternative, but also an inclusive and transformative economic empowerment instrument. To support the sustainability of this program, service optimization, ongoing education, and strengthening social relations between banks and business actors are needed. Sharia KUR has great potential to accelerate the growth of MSMEs that is fair, sustainable, and in accordance with Islamic economic principles.